Synthesis and Characterization of Grafted Chitosan Blending with Polyvinyl alcohol / Nanocomposite and Study Biological Activity - Ruwaidah S. Saeed; Hanaa G. Attiya; Kawther Ayad Obead (Baghdad Science Journal, 2023)
The study of biopolymers and their derivative materials had received a considerable degree of attention from researchers in the preparation of novel material. Biopolymers and their derivatives have a wide range of applications as a result of their bio-compatibility, bio-degradability and non-toxicity. In this paper, chitosan reacted with different aldehydes(2,4 –dichloro- benzaldehyde or 2-methyl benzaldehyde), different ketones (4-bromoacetophenone or 3-aminoacetophenone) to produce chitosan schiff base (1-4) . Chitosan schiff base (1-4) reacted with glutaric acid or adipic acid in acidic media in distilled water according to the steps of Fischer and Speier to produce compounds (5-12) respectively. Grafted chitosan (5-12) blended with synthetic polymer PVA to produce compounds (13-20), then these polymers were blended with nano Ag by using a hotplate stirrer for 60 min to produce nanocomposites. The synthesized polymers were identified via spectral analysis techniques, including FTIR , 1H-NMR and scanning electron microscope (SEM). Finally, studied anti-bacterial activities of some of the prepared polymers.